Regime Shifts in an Early Triassic Subtropical Ecosystem - Schneebeli-Hermann, Elke (Frontiers in Earth Science, 2020)
The Early Triassic was one of the most remarkable time intervals in Earth History. To begin with, life on Earth had to face one of the largest subaerial volcanic degassing, the Siberian Traps, followed by a plethora of accompanying environmental hazards with pronounced and repeated climatic changes. These changes not only led to repeated and, for several marine nektonic clades, intense extinction events but also to significant changes in terrestrial ecosystems. The Early Triassic terrestrial ecosystems of the southern subtropical region (Pakistan) are not necessarily marked by abrupt extinction events but by extreme shifts in composition. Modern ecological theories describe such shifts as catastrophic regime shifts. Here, the applicability of modern ecological theories to these past events is tested. Abrupt shifts in ecosystems can occur when protracted changing abiotic drivers (e.g. climate) reach critical points (thresholds or tipping points) sometimes accentuated by stochastic events. Early Triassic terrestrial plant ecosystem changes stand out from the longer term paleobotanical records because changes of similar magnitude have not been observed for many millions of years before and after the Early Triassic. To date, these changes have been attributed to repeated severe environmental perturbations, but here an alternative explanation is tested: the initial environmental perturbations around the Permian–Triassic boundary interval are regarded here as a main cause for a massive loss in terrestrial ecosystem resilience with the effect that comparatively small-scale perturbations in the following ~5 Ma lead to abrupt regime shifts in terrestrial ecosystems.